Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Grup Investigasi Terhadap Motivasi Belajar Siswa Pendidikan Agama Kristen Budi Dan Pekerti Kelas VIII SMP Negeri 3 Tarutung Tahun Pembelajaran 2023/2024 - Astritien Romauli Hutagalung (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this research is to determine the influence of the investigative group type Cooperative Learning model on the Learning Motivation of Christian Religious Education and Character of Class VIII Students of SMP Negeri 3 Tarutung for the 2023/2024 Academic Year. The method used in this research is a quantitative research method. The population is all 179 students of class VIII of SMP Negeri 3 Tarutung who are Christians. The sample was taken from 25% of 179 class VIII students at SMP Negeri 3 Tarutung, namely 45 people. Data was collected using a positive closed questionnaire of 50 items. The results of data analysis showed that there was a positive and significant influence of the investigative group type Cooperative Learning Model on the Christian Religious Education Learning Motivation and Characteristics of class VIII students of SMP Negeri 3 Tarutung T.P 2023/2024. 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.535> rtable(a=0.05,n=45) = 0.294, thus it is known that there is a positive relationship between variable X and variable Y. b) Test significant relationship obtained t value = 4.915> ttable(a=0.05,dk=n-2=47). c) Test influence of regression determination (r2) = 28.62%. 2) Influence test: Regression equation test, obtained regression equation Ŷ=31.52 + 0.59X. Thus Ha is accepted and H0 is rejected. This research concludes that there is a positive and significant influence of the investigative group type of cooperative learning model on the learning motivation for Christian religious education and character of students in class VIII of SMP Negeri 3 Tarutung for the 2023/2024 academic year.